ChemInform Abstract: Clathrate Formation in the Systems Sr—Cu—Ge and Ba, Sr—Cu—Ge. Issue 36 (9th September 2014) - Zeiringer, I.; Moser, R.; Kneidinger, F.; Podloucky, R.; Royanian, E.; Grytsiv, A.; Bauer, E.; Giester, G.; Falmbigl, M.; Rogl, P.
Abstract A novel clathrate type‐I phase, Sr8CuxGe46‐x (5.2 ≤ x < 5.4), is detected in arc melted ingots which exists close to the Zintl limit in a small temperature interval.